The Effect of performance appraisal on employee performance at the University of KwaZulu-Natal - Mulidzwi, Fulufhelo; Vajeth, Taahir; Mashau, Pfano (Penerbit Universiti Kebangsaan Malaysia, 2024)
Performance appraisal (PA) is commonly used to manage as well as to measure employees’ performance at various organisations. Large or small organisations are always seeking much better ways to effectively enhance and improve employee performance thus maximising profit. The main aim of the study was to investigate the effect of PA on employee performance at the University of KwaZulu-Natal (UKZN). The hypothesis for this study was that the PA process will have a positive impact on employee performance at the UKZN while the null hypothesis was that the PA process will not have any impact on employee performance at the UKZN. The study employed a quantitative research method. The study also used a descriptive research design to help the researcher describe the characteristics of the population in an accurate and systematic approach. A stratified random sampling technique was employed, employees were divided and categorised into groups representing departments or schools they belong to, and then a simple random sampling in each group was applied. The sample size was determined to be 225 academic and support staff. Findings showed that PA has a positive impact on employee performance at UKZN. The study recommends that managers and supervisors must continue to set clear work goals and work targets for their employees as it is noted that employees are more effective and highly motivated when they know what is required from them and their work target. Appraisers must give frequent feedback to employees and help them improve in areas where they are lacking.